Development of Polymer Electrolyte and Cathode Material for Li-Batteries. Issue 3 (19th December 2018) - Gupta, Himani; Singh, Shishir K.; Singh, Varun K.; Tripathi, Alok K.; Srivastava, Nitin; Tiwari, Rupesh K.; Mishra, Raghvendra; Meghnani, Dipika; Singh, Rajendra Kumar
Abstract : Enhancing the capacity and energy density of Li-battery along with maintaining its cycle life is the major challenge for electrochemical devices. Focusing on the positive electrode of Li-battery, specific capacity and cycle life of the layered oxide active material is studied thoroughly. On comparing their properties it could be found that Ni-rich layered oxide cathode materials give the best performance in terms of specific capacity and energy density but LiNi0.6 Mn0.2 Co0.2 O2 cathode provides good capacity along with sufficient cycling performance. So, it is optimized as cathode material with our prepared ionic liquid (IL) based polymer electrolyte for Li cell. The structure and morphology of synthesized cathode material along with the electrochemical performance of polymer electrolyte and cell are investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM) and electrochemical analyzer. Good specific discharge capacity (∼137 mAh g −1 ) and cyclability (upto 150 cycles) of the cell is observed. Experimental results suggest that the synthesized polymer electrolyte and cathode material is a promising candidate for Li battery.